Emotion and conflict : how human rights can dignify emotion and help us wage good conflict - Lindner, Evelin, 1954- (Contemporary psychology (Praeger Publishers), 2009)
Lindner takes us across history and into countries worldwide showing the role of emotion in hierarchies of domination and subjugation.